INTEGRATED CLASSIFICATION MODEL IN PUBLIC COMPLAINT MANAGEMENT IN THE KARAWANG DISTRICT INSPECTORATE - Kharisma Nourma Rani (RADJA PUBLIKA, 2026)
Public complaint management is a critical instrument for strengthening accountability, responsiveness, and supervisory quality in local government. This article analyzes the implementation of public complaint management at the Inspectorate of Karawang Regency and formulates an integrated classification model that connects the normative basis of complaints with operational priorities for follow-up actions. The study employed a descriptive qualitative approach using document review, process observation, and analysis of complaint data from 2023 to 2025. The data were analyzed through an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that complaint management has been supported by multiple reporting channels, particularly the Tangkar application and written letters, yet it still faces challenges in complaint classification, interpretation of completion status, and the high proportion of complaints closed administratively. Of 130 complaints recorded between 2023 and 2025, only 15 complaints, or 11.5%, were followed up through special audit or investigative mechanisms, while 115 complaints, or 88.5%, were archived or administratively closed. These findings indicate the need for a classification model that distinguishes supervisory and non-supervisory complaints while mapping urgency and importance using the Eisenhower Matrix. The proposed model assigns complaints into four follow-up priorities to support more consistent, transparent, and accountable decision-making.